Teacher preparation in Malaysia: needed changes - Goh, Pauline Swee Choo; Blake, Damian (Teaching in higher education, 2015)
The article attempts to present personal views of some changes that are needed to be made within teacher education in Malaysia. It uses one teacher education university as a point of reference to forward concerns. The university remains anonymous as it is not the intent of the article to critique the university but rather to highlight the more general challenges in preparing preservice teachers and to explore some approaches to improve teacher education within this university and its setting. The article starts by drawing together a set of concerns that face the field, arguing that three changes are needed to improve teacher preparation, namely (1) a curriculum that is grounded in the Malaysian context, (2) an improved practicum experience, and (3) to develop and situate practices in the schools. It concludes that the efforts to change within teacher education will not be easy, but needful; else the ultimate losers are the future teachers and their students.